It’s All Because of the Classics: Yesterday’s Today’s Inspiration Cinderella Wore A Modern Dress - Ignacio, Lourdes D. (Future Science / FSH-PH Publications, 2023)
The Classics remain to be an inspiration for modern works of art. One typical example is the Classic fairy tale Cinderella which has been retold and reimagined in various ways but has maintained its Classic flavor that blends well with its modern recipes. In our highly digitized world, the Classics are depicted in a modern format called the visual novel. This study tackled Victor Shklovsky’s defamiliarization to show the familiar and unfamiliar in a modern recommunicated version of Cinderella known as Cinders, a visual novel digital platform demonstrating how this contemporary work of art is inspired by the Classics. Likewise, this paper is hinged on Stephen Jay Greenblatt’s New Historicism framework to investigate the historical developments of a Classic tale like Cinderella evolving into its eponym Cinders who wears the modern dress of a visual novel in conformity with the Millennial fashion of digitized fairy tale writing’s format, platform, and presentation. The use of Karl Marx’s and Friedrich Engel’s Cultural Materialism in this study proves how perspectives about material wealth are being differently viewed by key characters as they vigorously pursue their personal goals. Melding with these literary frameworks is the researcher’s improvisation of three (3) guiding stars as the compass that helped uncover Cinders’s Classic spark, Classic vestiges, and Millennial or Contemporary Differences from its Classic inspirer Cinderella. Finally, this undertaking discussed the contrasts between book reading of a Classic work including the digital reading and playing of a Classic reincarnated version to cap this researcher’s scholarly journey.